Practices: an epistemological, ethical, political and didactic conception in the teacher training (Praxis Educativa, 2012)
To include practices in the teacher training of our University has been a controversial topic with a vision mainly “depending on application” regarding the practice field: first, students must learn theory, then (in the last year), practices must be done to transfer all that amount of theory to the practice. The aim of this paper is to present the model of ATT (Articulated Teacher Training) studied through Action Research in the last two decades, which includes the practices as an epistemological, ethical, political and didactic core of change. What do students learn in these practices? Which is the situated reality of the classroom? In these interactions they learn to use the practical reasoning in front of real problems which challenge them to consider possibilities, to discuss, to give their opinions and to take decisions. They also learn –as Arendt states– to live together, ones and others with diversity, to “build” together; basic political training that guides youth towards peace defense and against injustice.
Keywords: teacher training; practice; theory; deliberation; moral responsibility